2022
DOI: 10.3390/ijfs10020026
|View full text |Cite
|
Sign up to set email alerts
|

The Moderating Effects of Host Country Governance and Trade Openness on the Relationship between Cultural Distance and Financial Performance of Foreign Subsidiaries in Latin America

Abstract: Cultural distance (CD) is an important driver of foreign expansion strategy at the firm level. However, its effects can be more or less significant depending on the contextual characteristics of the host country, such as the quality of formal institutions and the openness to international trade. Therefore, it is argued that strong formal institutions in the host country can effectively reduce the adverse impact of CD. Additionally, due to the more frequent interactions with foreign cultures, countries open to … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 59 publications
0
14
0
Order By: Relevance
“…By highlighting the specific effects of the host cultural profile, we propose that CD studies that focus on a single host country are biased towards the specific effects that relate to the overall cultural traits of the host country's environment. The specific effects of different cultural profiles in the host country help explain the asymmetric effects of CD identified in the IB literature (;Correa da Cunha, 2019;Correa da Cunha et al 2022;Magnani et al, 2018;Selmer et al, 2007).…”
Section: Contributions To Literature and Theorymentioning
confidence: 99%
“…By highlighting the specific effects of the host cultural profile, we propose that CD studies that focus on a single host country are biased towards the specific effects that relate to the overall cultural traits of the host country's environment. The specific effects of different cultural profiles in the host country help explain the asymmetric effects of CD identified in the IB literature (;Correa da Cunha, 2019;Correa da Cunha et al 2022;Magnani et al, 2018;Selmer et al, 2007).…”
Section: Contributions To Literature and Theorymentioning
confidence: 99%
“…the discordance assumption) has been challenged as there seems to be evidence that in some cases cultural differences might lead to innovation and superior performance (Boschma, 2005; Vaccarini et al, 2017). The illusion of symmetry has been addressed by studies that indicate that depending on the observers’ perspective, the effects of CD might in fact be asymmetric (Correa da Cunha, 2019; Magnani et al, 2018; Selmer et al, 2007). Still, some argue that the commonalities (or differences) between home and host countries is what really matters (Williams and Grégoire, 2015), while others challenged the assumption of linearity as the psychic distance paradox suggests that a shorter distance can in fact represent a disadvantage as the “perceived similarity can lead to carelessness and failure” (O'Grady and Lane, 1996: 329).…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…KS composite index) which seems to emphasize the liability implications of CD (Beugelsdijk et al, 2018). Nevertheless, a few more recent studies have shown that in some cases, CD can lead to positive outcomes (Boschma, 2005; Vaccarini et al, 2017), which might depend on a combination of different dimensions of CD in specific directions (Stor, 2021), therefore emphasizing the nonequivalent and asymmetric characteristics of the construct (Correa da Cunha, 2019; Magnani et al, 2018; Selmer et al, 2007; Shenkar, 2001; Zaheer et al, 2012).…”
Section: Final Considerationsmentioning
confidence: 99%
“…The impact of cultural context in business practices is shown to be very relevant and can explain a wide range of organizational phenomena (Gallego-Álvarez and Ortas, 2017). Indeed, research on this issue considers Hofstede's pioneer national cultural model (1983) and its cultural dimensions still valid (Correa da Cunha, 2019). Specifically, cultural values affect the way sustainability is perceived in a society and thus within business practices (Laurell et al.…”
Section: Research Relevance and Justificationmentioning
confidence: 99%